Equity in Basic Medical Education accreditation standards: a scoping review protocol - Usman Mahboob; Muhammad Irfan; Neelofar Shaheen; Ahsan Sethi (BMJ Open)
Introduction Accreditation in Health Professions Education is a pivotal process to ensure the quality of medical institutions and health professionals. ‘Equity’ is an umbrella term reflecting the principles of justice and support to disadvantaged entities according to their needs. While commonly applied to various domains in medical education, there is potential to determine how ‘equity’ is considered or discussed while practically implementing accreditation standards for Basic Medical Education (BME) globally.Methods and analysis The scoping review protocol has been drafted in compliance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses-Protocol (PRISMA-P) checklist. We will conduct a planned scoping review according to the Joanna Briggs Institute (JBI) guidelines for scoping review and adhere to the PRISMA-Scoping Review extension (PRISMA-ScR) checklist. A systematic literature search, from inception to May 2024, will be conducted across search engines and databases including Google Scholar, PubMed, Web of Science, Wiley Online Library and ProQuest, in collaboration with a qualified librarian. Peer-reviewed research articles, commentaries, opinion papers and reviews that explicitly or implicitly discuss equity in reference to accreditation standards will be eligible for inclusion. A qualitative inductive thematic analysis will be employed to systematically identify categories and themes from the extracted data and draw conclusions.The review team anticipates the development of a conceptual map that will evolve during the synthesis of the literature, as a description of the term ‘equity’ in the implementation of BME accreditation standards. We also anticipate finding any methodological or theoretical framework that is used in the literature to discuss the concept of ‘equity’ in the implementation of BME accreditation standards.Ethics and dissemination This scoping review aims to systematically map the literature on the burgeoning domain of accreditation in BME. The scoping review entails the collection and synthesis of literature and does not require ethical approval as per local regulations, as it does not involve primary data collection or interaction with human participants. The research findings will be disseminated through peer-reviewed publications, social media platforms, and academic presentations at workshops and conferences.